Risk Mitigation Analysis of Wet Cocoa Beans Supply Chain in North Luwu Regency - Kamal, Winda; Kristanti, Novita Erma; Sukartiko, Anggoro Cahyo (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2025)
Cocoa in North Luwu Regency is contributing greatly to the improvement of the economy. However, different factors have caused a decrease in the amount of production since 2019 and farmers mostly sell cocoa as wet beans. Therefore, this research aimed to reduce the impact of risk on the supply chain of North Luwu wet cocoa beans through Supply Chain Risk Management, which included the stages of mapping, risk identification, analysis, and mitigation. The results showed that the supply chain flow map was obtained by tracing and identifying the tiers using snowball sampling method. Subsequently, the list of risk for each tier was identified and assessed for the likelihood, severity, and detection levels through in-depth interviews using 5 Likert scales. Data analysis was also carried out by determining the mapping matrix in avoid, transfer, manage, and appetite risk, as well as assessing the Risk Priority Number (RPN). Avoid risk and those with a high RPN value were priorities in preparing mitigation. The stages considered were the interview and group discussion with risk owners and experts. Meanwhile, the flows of the wet cocoa bean supply chain were identified. In the farmer tier, 8 risks, 10 collectors, 9 cooperatives, and 9 industries were reported. High rainfall, classified as avoid risk, had the highest RPN value. This risk was identified in almost all tiers and mitigated through irrigation improvements, reservoir construction, and planting new adaptive clones.